Pemberdayaan Masyarakat Bagi Kader Lansia Dalam Penguatan Ems (Emergency Medical System) Psc (Public Safety Center) 119 Dalam Peningkatan Manajemen Prehospital Pasien Stroke Di Desa Karangsoko Di Wilayah Kerja Puskesmas Trenggalek Kabupaten Trenggalek - Yuswantoro, Edi; Ixora, Ixora; Christiani, Mimik (Politeknik Kesehatan Kemenkes malang, 2024)
Stroke ( CVA) is the second leading cause of death and the third leading cause of disability in the world. The increase in death and disability rates is caused by delays in treating stroke due to hospital delays. The result of the study showed that the time from the onset of a stroke to a visit to the hospital was the biggest contributor to delays in stroke treatment from the start of the attack, a preliminary study conducted at the trenggalek community health center in 2020 showed that the number of stroke incidents in the trenggalek community health center work area tended to increase from 131 cases in 2020 to i43 cases and 51 cases (36%) came from karangsoko village. The incidence of hypertension in karangsoko village is the highest, namely 335 cases (30%) out of 1.136 cases. Data on the incidence of hypertension shows that residents are at risk of stroke. Hypertension is the most important and consistent risk factor. The introduction of stroke and activation of the emergency medical system (EMS) through detection, dispatch and delivery for prehospital stroke treatment is expected to reduce the number of disabilities and deaths due to stroke attacks due to delays in the prehospital emergency medical system (PSC) is the main part of the SPGDT which organizes coordination and emergency services located at the city district level, based on this description, it is necessary to carry out community service regarding strengthening the EMS ( Emergency medical system) PSC (Public safety center) 119 in improving the prehospital management of stroke patients in karangsoko village.